Fiscal Policies for Job Creation and Innovation: The Experiences of US States - Robert S. Chirinko; Daniel J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper reviews selected fiscal policy initiatives undertaken by US states to encourage job creation and innovation. We begin with a discussion of some general considerations about the design of tax policies summarized in a tax policy design table. Four policies are reviewed: job creation tax credits, research and development tax credits, a set of tax policies targeted to the biotechnology industry, and a broad set of tax policies that attract star scientists. The experiences at the state level are used to evaluate the effectiveness of these employment and knowledge-capital tax incentives in creating jobs and spurring innovation. The paper concludes with four other considerations need to be taken into account in selecting policies.
Keywords: H71; H25; 330; targeted state fiscal policies; employment tax incentives; job creation; knowledge-capital tax incentives; innovation